2009
DOI: 10.1080/14702540902873915
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Landscapes of the Improvement Period: Surveys of North Lochtayside, 1769 and 2000

Abstract: The thousands of plans of Scottish estates produced in the late-eighteenth and earlynineteenth centuries comprise a resource of huge potential for the study of the development of the Scottish rural landscape. These plans become all the more important once it is appreciated that in some parts of Scotland elements of eighteenth-century landscapes have survived two centuries of improvement, and can be studied on the ground as well as in map archives. Using the example of RCAHMS fieldwork on Lochtayside, Perthshir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The importance of maps for registration of the property is the theme of essays by David Fletcher and Laura Federzoni (Fletscher 1998; Federzoni 2013); however, the meaning of the landscape and its development remains overshadowed in these works. The potential comparison of this type of map with other materials has been noted by Steve Boyle, who compared a map of a Scottish estate from 1769 with local archaeological research data (Boyle 2009). These individual maps, however, are important not only for this knowledge.…”
Section: The Number Of Archive Resources With a Larger Amount Of Extamentioning
confidence: 99%
“…The importance of maps for registration of the property is the theme of essays by David Fletcher and Laura Federzoni (Fletscher 1998; Federzoni 2013); however, the meaning of the landscape and its development remains overshadowed in these works. The potential comparison of this type of map with other materials has been noted by Steve Boyle, who compared a map of a Scottish estate from 1769 with local archaeological research data (Boyle 2009). These individual maps, however, are important not only for this knowledge.…”
Section: The Number Of Archive Resources With a Larger Amount Of Extamentioning
confidence: 99%
“…The impact changes in land-use had on the archaeological record in Scotland are frequently cited (e.g. Dixon and Gannon, 2008;Boyle, 2009), but quantifying or mapping that impact has only recently been undertaken on a wider scale or in a systematic manner (see above; Dixon, 2007). It is well-established that drainage can result in the near total loss of archaeological sites and materials (Chapman and Cheetham, 2002).…”
Section: Drainage and Impacts To The Archaeological Recordmentioning
confidence: 99%
“…In order to quantify loch drainage, this study used historic mapping as its primary source of information. Cartography was an essential part of the agricultural changes that began in the 18 th century, as large estates sought to maximize economic productivity of their land and tenants (for discussion see Adams, 1968;Boyle, 2009). In addition to estate mapping, there was also an increase in mapping at regional and national scales.…”
Section: The Roy Military Survey Of Scotland (1747-1755)mentioning
confidence: 99%
“…21 http://www.benlawers.org.uk/ Although an excellent achievement in getting to grips with shielings and peripheral settlements on the outfield areas, less attention was devoted to the settlement foci and it still remains an unfulfilled aspiration to excavate a highland rural settlement focus in extenso. Recent survey work by RCAHMS as part of the Project has updated and refined this analysis, and shown that there is a degree of continuity in settlement from the mid-18 th century through the Improvement Period to the later-19 th century in the settlement foci (Boyle 2003(Boyle , 2009. Research into medieval settlement in the Northern and Western Isles has increasingly focused on Scandinavian settlement.…”
Section: Settlement and The Materials Culture Of Daily Lifementioning
confidence: 99%